Impact of vasomotion type on prognosis of coronary artery spasm induced by acetylcholine provocation test of left coronary artery. (February 2017) - Lee, Eun Mi; Choi, Man Ho; Seo, Hong Seog; Kim, Hyun Ki; Kim, Nam-Ho; Choi, Cheol Ung; Kim, Jin Won; Lim, Hong Euy; Kim, Eung Ju; Rha, Seung-Woon; Park, Chang Gyu; Oh, Dong Joo
Abstract: Background and aims: The impact of vasomotion types on long-term clinical outcomes in patients with coronary artery spasm (CAS) induced by the acetylcholine provocation test (ACH-test) remains unclear. Methods: We evaluated 4644 consecutive patients with typical resting chest pain (CP), but no angiographically significant coronary artery lesion (<50% stenosis), who underwent an ACH-test. According to their vasomotor response, patients were categorized into four types: normal vasomotion (no CP, no ischemic electrocardiographic changes, and no vasoconstriction), microvascular spasm (CP with <75% vasoconstriction but with CP relief after nitroglycerin infusion), epicardial spasm (CP with ≥75% vasoconstriction), and ACH-test inconclusive (vasoconstriction and/or electrocardiographic changes, but no CP). We investigated CP recurrence requiring follow-up angiography and major adverse cardiovascular events (MACEs) during 5 years. Results: CP recurred in 7.9% of patients and was more frequent in abnormal vasomotion types (normal vasomotion, microvascular spasm, epicardial spasm, and inconclusive type: 5.4%, 9.8%, 10.9%, and 8.2%, respectively, log-rank p = 0.009). In multivariate analysis adjusted for medication use after the ACH-test, vasomotion subtype was not an independent predictor, whereas male sex, fixed lesion on baseline angiography, and medications including calcium channel blockers (CCBs), nitrates, and statins were independent positive predictors for recurrent CP. Alcohol consumption at the initial interview was a negative predictor. MACEs were observed in 1.6%, and the incidence was similar among subtypes ( p = 0.421). Conclusions: Recurrent CP and long-term outcomes are independent of vasomotion subtypes, but long-term use of CCBs, nitrates, and statins is a significant predictor for recurrent CP. Highlights: Impact of vasomotion types on chest pain and outcomes is evaluated. Chest pain is more frequent in epicardial spasm type. The overall rate of major adverse cardiovascular events (MACEs) is very low, similar between subtypes.